EUROPEJSKI NAKAZ OCHRONY – ISTOTA I ZNACZENIE - Bieńkowska, Ewa (Zeszyty Prawnicze, 2016)
EUROPEAN PROTECTION ORDER – ITS ESSENCE AND IMPORTANCE Summary The paper analyses provisions of the Directive of the European Parliament and the Council 2011/99/EU of 13 December 2011 on the European protection order. It concludes that European protection order can be not strong enough to protect victims in the cross-border situations. The main reason of its “illness” is a lack of obligation for member states to have (or introduce) in their penal law systems measures of protection of victims, as a basis for the order, like described in Article 5 of the Directive.